A SiBCN / DLC gradient film and preparation method thereof

Through the preparation method of SiBCN/DLC gradient film, the problem of internal stress and hidden cracks generated during the deposition process of DLC film is solved, the hardness and film-based binding force of the film are improved, the service life is extended, and high density and good optical permeability are achieved.

CN115874143BActive Publication Date: 2025-03-28HAINAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211630755.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-03-28
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The existing DLC ​​films generate internal stress and hidden cracks during the deposition process, causing the film to fall off and do not match the chemical properties of the glass substrate, affecting the film-based binding force and reducing service life.

Method used

By using the preparation method of SiBCN/DLC gradient film, the SiBCN target and C target are surface pretreated, and the SiBCN target and C target are sputtered simultaneously in the magnetron sputtering chamber, the decreasing and increasing sputtering power are controlled to form a SiBCN/DLC gradient film.

Benefits of technology

It improves the hardness and film-based bonding force, reduces internal stress and hidden cracks, extends service life, and has high density and good optical transmissibility. It is suitable for protective layers of optical devices and electronic display screens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004005659390000011
    Figure HDA0004005659390000011
  • Figure HDA0004005659390000012
    Figure HDA0004005659390000012
  • Figure HDA0004005659390000021
    Figure HDA0004005659390000021
Patent Text Reader

Abstract

The present invention provides a method for preparing a SiBCN / DLC gradient film, comprising the following steps: A) performing surface pretreatment on a substrate, a SiBCN target material, and a C target material respectively; B) placing the SiBCN target material and the C target material in a magnetron sputtering chamber, sputtering the SiBCN target material and the C target material simultaneously, and within the same sputtering time and the same sputtering power range, the sputtering power of the SiBCN target material decreases, and the sputtering power of the C target material increases, thereby obtaining a SiBCN / DLC gradient film. The present application also provides a SiBCN / DLC gradient film prepared by the above method. The SiBCN / DLC gradient film prepared by the present application has high density, good optical transmittance, good mechanical properties and a low friction coefficient, and can be used as a protective layer for optical devices and electronic display screens.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective films, and in particular to a SiBCN / DLC gradient film and a preparation method thereof. Background Art

[0002] Frictional wear is a common phenomenon in the industrial field and daily life. The main reasons for this phenomenon are physical and chemical. The physical aspect includes adhesive wear, abrasive wear and fatigue wear, etc. These wears are caused by the uneven surface of the material or deformation caused by external forces, resulting in cracks on the surface and separation of micro-flakes or particles; the chemical aspect includes corrosive wear, and corrosive wear often occurs on the metal surface. The metal reacts chemically or electrochemically with the surrounding medium at the same time, so that corrosion and wear work together to cause the loss of material on the surface of the parts. It is particularly important to reduce frictional wear in industrial production.

[0003] Diamond-like carbon (DLC) film is a graphite-structured sp 2 —C and sp of diamond structure 3 The amorphous structure formed by C hybridization has a series of advantages such as high hardness, low friction coefficient, good chemical inertness and the ability to effectively improve the friction and wear properties of the substrate surface. It is widely used in surface engineering fields such as automobiles, gears, mobile phone screens and cutting tools.

[0004] However, the DLC film will generate large internal stress during the deposition process, which increases its internal defects and produces hidden cracks. When subjected to external friction, the hidden cracks gradually expand and eventually cause the film to fall off. In addition, the mismatch between the chemical properties of the DLC film and the glass substrate will also affect the film-base bonding strength and reduce the service life of the glass. Therefore, many scholars have begun to study it, and have released the residual stress of the DLC film by changing process parameters, doping, and other methods, and continuously improved its film-base bonding strength. The problem of weak bonding caused by the mismatch of the film-base chemical properties can be effectively alleviated by adding a transition layer, and the addition of multiple gradient transition layers can further alleviate the film-base difference and improve the film-base bonding strength, making the film less likely to fall off.

[0005] A Chinese patent with publication number CN 109797370 A discloses a glass-based DLC composite hardening film that transmits visible light and a preparation method thereof. The method is to deposit a silicon oxycarbide transition layer and a DLC layer on the surface of a glass substrate using a magnetron sputtering process. The transition layer structure has Si-C bonds, Si-O-Si bonds and CC bonds. The silicon oxycarbide surface formed on the glass substrate produces a sawtooth cavity, which has good hardness and film-base bonding while meeting optical properties.

[0006] A Chinese patent with application number 201810091973.9 discloses a DLC film hardened glass and a preparation method thereof. A SiO2 / SiC / DLC film is plated on a glass substrate by magnetron sputtering. However, the DLC film is relatively thick, which will increase the internal stress of the film, and the film transmittance is not mentioned.

[0007] A Chinese patent with publication number CN 108149193 A discloses a diamond-like carbon-based film and a preparation method thereof. A SiO2 / Cu-DLC film is prepared on a substrate by magnetron sputtering. The bonding strength between the DLC film and the substrate is enhanced by adding a SiO2 transition layer. The bonding strength between the film and the substrate is reduced by doping, but the film structure is affected, resulting in a decrease in hardness.

[0008] In terms of preparation technology, the most common methods are chemical vapor deposition and physical vapor deposition. Magnetron sputtering technology belongs to physical vapor deposition. Compared with chemical vapor deposition, magnetron sputtering has the advantages of dense film and high surface smoothness. In addition, under many conditions of chemical vapor deposition, the reaction sources participating in the deposition and the residual gases of the reaction are flammable, explosive or toxic, so some corresponding measures need to be taken.

[0009] From the perspective of film layer design, it is undeniable that the traditional multilayer film with fixed element content can effectively improve the problem of weak bonding, but there are still differences in chemical properties, thermal expansion coefficients, sudden changes in the content of each element, and interface effects between the film layers. Therefore, it is of great significance to provide an appropriate gradient multilayer film to replace the ordinary film layer with fixed element content to achieve excellent bonding and anti-wear and wear-reducing properties of the film. Summary of the invention

[0010] The technical problem solved by the present invention is to provide a method for preparing a SiBCN / DLC gradient film. The SiBCN / DLC gradient film prepared by the method has higher hardness and greatly increased service life.

[0011] In view of this, the present application provides a method for preparing a SiBCN / DLC gradient film, comprising the following steps:

[0012] A) performing surface pretreatment on the substrate, SiBCN target and C target respectively;

[0013] B) The SiBCN target and the C target are placed in a magnetron sputtering chamber, and the SiBCN target and the C target are sputtered simultaneously. Within the same sputtering time and the same sputtering power range, the sputtering power of the SiBCN target decreases, and the sputtering power of the C target increases, thereby obtaining a SiBCN / DLC gradient film.

[0014] Preferably, the surface pretreatment of the substrate is specifically as follows:

[0015] The substrate was ultrasonically cleaned with detergent, acetone, alcohol and ultrapure water, and dried with nitrogen.

[0016] Preferably, the surface pretreatment of the SiBCN target and the C target is specifically as follows:

[0017] The SiBCN target and the C target are placed in a vacuum chamber at the same time, the vacuum degree is set to 0.75-1.25 Pa, the argon gas flow rate is set to 30-60 sccm, the sputtering power is set to 95-105 W, and the sputtering is performed for 10-20 minutes.

[0018] Preferably, in step B), during the sputtering process, the magnetron sputtering chamber is evacuated to a vacuum of 1.5×10 -3 ~2.5×10 -3 Pa, temperature is 50-80℃, holding time is 10-20min, argon flow rate is 30-40sccm; adjust the butterfly valve to make the sputtering pressure 1-1.5Pa, and control the pressure for 10-20min.

[0019] Preferably, in step B), the sputtering power of the SiBCN target is 130-60W, and the sputtering power of the C target is 60-130W.

[0020] Preferably, in step B), the sputtering time of the SiBCN target and the C target is 90 min.

[0021] Preferably, in step B), the process of simultaneously sputtering the SiBCN target and the C target is specifically as follows:

[0022] The sputtering power of target C was uniformly increased from 60W to 130W within 45min, and then uniformly decreased from 130W to 60W within 45min.

[0023] At the same time, the sputtering power of the SiBCN target was uniformly reduced from 130W to 60W within 45min, and then uniformly increased from 60W to 130W within 45min.

[0024] Preferably, in step B), the process of simultaneously sputtering the SiBCN target and the C target is specifically as follows:

[0025] The sputtering power of target C was uniformly increased from 60W to 130W within 30min, then uniformly decreased from 130W to 60W within 30min, and finally uniformly increased from 60W to 130W within 30min;

[0026] The sputtering power of the SiBCN target was uniformly reduced from 130 W to 60 W within 30 min, then uniformly increased from 60 W to 130 W within 30 min, and finally uniformly reduced from 130 W to 60 W within 30 min.

[0027] The present application also provides a SiBCN / DLC gradient film prepared by the preparation method, wherein the elements and element contents of each layer of the SiBCN / DLC gradient film vary in a gradient.

[0028] Preferably, the SiBCN / DLC gradient film has 1 to 4 layers and a thickness of 450 to 550 nm.

[0029] The present application provides a method for preparing a SiBCN / DLC gradient film, which is obtained by simultaneously sputtering a SiBCN target and a C target, and uniformly increasing or decreasing the sputtering power within a specific time; the multilayer gradient film prepared by the present application allows continuous changes in structure and content between each film layer, can form a transitional bonding area, alleviate lattice differences and thermal expansion coefficient mutations, and the element diffusion between the film layers forms a structure similar to a mechanical lock, which makes the bonding between the film layers tighter and stronger, greatly increasing the service life of the film; at the same time, the selection of SiBCN ceramics in the present application allows the five elements Si, O, B, C, and N to exist in the film in the form of mutual bonding, and the content of Si-C bonds is as high as 47%, and the content of N elements is 7.4%. At the same time, the appearance of BC and BCN bonds indicates that the DLC film may form structures such as boron carbide and boron nitride in its growth direction. Such structures are inorganic materials with relatively high hardness at room temperature, thereby improving the overall hardness of the film. Therefore, the film prepared by the present invention has high density, good optical transmittance, good mechanical properties and low friction coefficient, and can be used as a protective layer for optical devices and electronic display screens. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The scanning electron microscope images of the surface and cross section of the SiBCN / DLC gradient film prepared in Examples 1 to 4;

[0031] Figure 2 The Raman spectra of the SiBCN / DLC gradient films prepared in Examples 1 to 4;

[0032] Figure 3 The nano-scratch behavior and residual morphology of the SiBCN / DLC gradient films prepared in Examples 1 to 4;

[0033] Figure 4 The friction and wear diagram of the SiBCN / DLC gradient films prepared in Examples 1 to 4;

[0034] Figure 5 Vickers hardness indentation morphology of SiBCN / DLC gradient films prepared in Examples 1 to 4;

[0035] Figure 6 The UV-visible light transmission spectra of the SiBCN / DLC gradient films prepared in Examples 1 to 4. DETAILED DESCRIPTION

[0036] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0037] In view of the technical problem that the layers of the gradient film in the prior art are not tightly combined and are discontinuous, the present application provides a SiBCN / DLC gradient film and a preparation method thereof. The gradient in the SiBCN / DLC gradient film provided by the present application is the change in the content of each element and the size of the clusters in the film, which is continuous. Specifically, the embodiment of the present invention first discloses a preparation method of a SiBCN / DLC gradient film, comprising the following steps:

[0038] A) performing surface pretreatment on the substrate, SiBCN target and C target respectively;

[0039] B) The SiBCN target and the C target are placed in a magnetron sputtering chamber, and the SiBCN target and the C target are sputtered simultaneously. Within the same sputtering time and the same sputtering power range, the sputtering power of the SiBCN target decreases, and the sputtering power of the C target increases, thereby obtaining a SiBCN / DLC gradient film.

[0040] In the preparation process of SiBCN / DLC gradient film, the present application first performs surface pretreatment on the substrate, SiBCN target and C target respectively; the surface pretreatment of the substrate is specifically: the substrate is ultrasonically cleaned with detergent, acetone, alcohol and ultrapure water in succession, and blown dry with nitrogen.

[0041] The surface pretreatment of the SiBCN target and the C target is specifically as follows:

[0042] The SiBCN target and the C target are placed in a vacuum chamber at the same time, the vacuum degree is set to 0.75-1.25 Pa, the argon gas flow rate is set to 30-60 sccm, the sputtering power is set to 95-105 W, and the sputtering is performed for 10-20 minutes.

[0043] In the present application, the substrate can be specifically selected from a glass substrate, and its average visible light transmittance is 90%.

[0044] After the substrate and target material are pretreated, the present application places the SiBCN target and the C target in a magnetron sputtering chamber, and the SiBCN target and the C target are sputtered simultaneously. Within the same sputtering time and within the same sputtering power range, the sputtering power of the SiBCN target decreases, and the sputtering power of the C target increases, thereby obtaining a SiBCN / DLC gradient film. In this process, the SiBCN target and the C target are placed in the magnetron sputtering chamber at the same time, and sputtering is started at the same time; during the sputtering process, within the same sputtering time and within the same sputtering power variation range, the sputtering power of the SiBCN target and the sputtering power of the C target decrease or increase at the same sputtering rate, thereby obtaining a SiBCN / DLC gradient film. Specifically, before sputtering, the magnetron sputtering chamber is evacuated to 1.5×10 -3 ~2.5×10 -3 Pa, temperature is 50-80°C, holding time is 10-20min, argon flow rate is 30-40sccm; adjust the butterfly valve to make the sputtering pressure 1-1.5Pa, and control the pressure for 10-20min. According to the present invention, the sputtering time is 90min, and the sputtering power of the SiBCN target material varies in the range of 130-60W, and the sputtering power of the C target material varies in the range of 60-130W. More specifically, the sputtering power of the C target is uniformly increased from 60W to 130W within 45min, and then the sputtering power is uniformly reduced from 130W to 60W within 45min;

[0045] At the same time, the sputtering power of SiBCN target was uniformly reduced from 130W to 60W within 45min, and then uniformly increased from 60W to 130W within another 45min;

[0046] Or, the sputtering power of the C target is uniformly increased from 60W to 130W within 30min, then uniformly decreased from 130W to 60W within 30min, and finally uniformly increased from 60W to 130W within 30min;

[0047] The sputtering power of the SiBCN target was uniformly reduced from 130 W to 60 W within 30 min, then uniformly increased from 60 W to 130 W within 30 min, and finally uniformly reduced from 130 W to 60 W within 30 min.

[0048] The preparation method of the SiBCN / DLC gradient film of the present application is specifically as follows: using a PVD 500 high vacuum magnetron sputtering coating system, using an AE radio frequency power supply (13.56MHz) as a working power supply, argon (purity 99.995%) as a working gas, graphite (purity 99.999%) and SiBCN (atomic ratio: 2:1:2.5:1) as sputtering targets, and depositing a SiBCN / DLC gradient film on a glass substrate (average visible light transmittance 90%). The gradient film is achieved by sputtering two targets simultaneously, and the sputtering power is uniformly increased or decreased within a specified time.

[0049] The present application also provides a SiBCN / DLC gradient film prepared by the above method, wherein the elements and element contents of each layer of the SiBCN / DLC gradient film vary in a gradient.

[0050] The internal structure or element connection relationship of the SiBCN / DLC gradient film provided by the present invention is variable. The change rate of the target power in different examples is different (the change amount of sputtering power per unit time), which will affect the size of the target clusters bombarded (the greater the change rate of sputtering power, the greater the difference in cluster size), thereby changing the cluster stacking mode; on the other hand, it will affect the element content, which is also reflected in the gradient film. This gradient is the change in the content of each element and the change in cluster size.

[0051] The preparation method of SiBCN / DLC film provided by the present invention and the selection of SiBCN ceramics will make the five elements Si, O, B, C, and N exist in the film in the form of mutual bonding, and the content of Si-C bonds reaches up to 47%, and the content of N elements is 7.4%. At the same time, the appearance of BC and BCN bonds indicates that the DLC film may form structures such as boron carbide and boron nitride in its growth direction. Such structures are inorganic materials with high hardness at room temperature, which can improve the overall hardness of the film; the preparation of multi-layer gradient film makes the structure and content between each film layer change continuously, forming a transitional bonding area, alleviating lattice differences and thermal expansion coefficient mutations, and the diffusion of elements between the film layers forms a structure similar to mechanical locking, making the bonding between the film layers tighter and stronger, greatly increasing the service life of the film.

[0052] Therefore, the preparation process of the film of the present invention is reasonable, the film surface is uniform, the film thickness is about 500nm, and the film will not affect the performance due to the thick thickness; the prepared film has high density, good optical transmittance, good mechanical properties and low friction coefficient, and can be used as a protective layer for optical devices and electronic display screens. In addition, the present invention adopts the mature radio frequency magnetron sputtering technology to prepare the target film, which is simple to operate and is conducive to large-scale batch production in industry.

[0053] In order to further understand the present invention, the SiBCN / DLC gradient film and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0054] In the following examples, a laser Raman spectrometer is used to analyze the bond structure of the SiBCN / DLC film; a field emission scanning electron microscope (SEM) is used to analyze the surface morphology and cross-sectional thickness of the film; the transmittance of the film is tested using a UV-visible spectrophotometer; a multifunctional material mechanics testing system is used to analyze the friction coefficient and bonding force of the film; and a micro-Vickers hardness tester is used to analyze the hardness of the film.

[0055] Example 1

[0056] 1) A glass substrate (25.4×76.22 mm) was ultrasonically cleaned with detergent, acetone, alcohol, and ultrapure water for 30 min each, blown dry with nitrogen, and placed in a vacuum chamber together with the pre-cleaned target for standby use;

[0057] 2) Close the chamber door and pump the air pressure from the indoor pressure to 2.0×10 -3 After 1 Pa, argon gas is introduced into the chamber with a flux of 50 sccm. The butterfly valve is adjusted to control the pressure at 1 Pa. The bias power supply is adjusted to 500 V. The substrate is further cleaned by using the plasma generated by glow discharge and the argon ions bombarding the substrate under the action of the electric field.

[0058] 3) After cleaning, turn off the bias power supply and nitrogen valve, and continue to evacuate to 2.0×10 -3 Pa, turn on the graphite heater, and the temperature reaches 60℃. After controlling the temperature for 15 minutes, argon gas is introduced into the chamber with a flux of 30sccm. The butterfly valve is adjusted to control the pressure at 1.5Pa. After controlling the pressure for 15 minutes, the RF power supplies corresponding to the C target and the SiBCN target are turned on at the same time, and the powers are set to 60W and 130W respectively. The sputtering power of the C target is uniformly increased from 60W to 130W within 90 minutes, and the sputtering power of the SiBCN target is uniformly reduced from 130W to 60W within 90 minutes. After the experiment, the sample is naturally cooled to room temperature to obtain a single-layer SiBCN / DLC gradient film.

[0059] The performance of the gradient film prepared in this embodiment was tested, and the test results are as follows: Figure 1 to Figure 6 The results show that the film thickness is about 550nm. D / I GThe value is 0.929, the Vickers hardness is 782.9HV, the friction coefficient is 0.12, the maximum transmittance of the film in the visible light range is 97%, and the film-base bonding force is slightly damaged under a force of 200mN. As the load increases, strip cracks appear along the scratch track, but there is no large-scale peeling of the film.

[0060] Example 2

[0061] The method is basically the same as Example 1, except that: compared with step (3) in Example 1, the power of the C target and the SiBCN target changes with time differently; in Example 2, the sputtering power of the C target increases uniformly from 60 W to 130 W within 45 minutes, and then the sputtering power decreases uniformly from 130 W to 60 W within 45 minutes; at the same time, the sputtering power of the SiBCN target decreases uniformly from 130 W to 60 W within 45 minutes, and then the sputtering power increases uniformly from 60 W to 130 W within 45 minutes. After the experiment, the sample is naturally cooled to room temperature to obtain a double-layer SiBCN / DLC gradient film.

[0062] The performance of the gradient film prepared in this embodiment was tested, and the test results are as follows: Figure 1 to Figure 6 The results showed that the film thickness was about 500nm, the Vickers hardness was 770.3HV, the friction coefficient was 0.06, the maximum transmittance of the film in the visible light range was 93%, and the film-base bonding strength only showed signs of plastic deformation under a force of 200mN, and no cracks, breakage, or falling off were found.

[0063] Example 3

[0064] The method is basically the same as Example 1, except that: compared with step (3) in Example 1, the power changes of the C target and the SiBCN target with time are different. In Example 3, the sputtering power of the C target is uniformly increased from 60W to 130W within 30 minutes, and then the sputtering power is uniformly reduced from 130W to 60W within 30 minutes, and finally the sputtering power is uniformly increased from 60W to 130W within 30 minutes; at the same time, the sputtering power of the SiBCN target is uniformly reduced from 130W to 60W within 30 minutes, and then the sputtering power is uniformly increased from 60W to 130W within 30 minutes, and finally the sputtering power is uniformly reduced from 130W to 60W within 30 minutes. After the experiment, the sample is naturally cooled to room temperature to obtain a three-layer SiBCN / DLC gradient film.

[0065] The performance of the gradient film prepared in this embodiment was tested, and the test results are as follows: Figure 1 to Figure 6 The results show that the film thickness is about 500nm. D / I GThe value is 0.889, the Vickers hardness is 766.6HV, the friction coefficient is 0.1, the maximum transmittance of the film in the visible light range is 94%, and the film-base bonding force is slightly damaged after plastic deformation under a force of 200mN, but there is no falling off.

[0066] Example 4

[0067] The method is basically the same as Example 1, except that: compared with step (3) in Example 1, the power changes of the C target and the SiBCN target with time are different. In Example 4, the sputtering power of the C target is uniformly increased from 60W to 130W within 23 minutes, and then the sputtering power is uniformly reduced from 130W to 60W within 23 minutes, and then the sputtering power is uniformly increased from 60W to 130W within 23 minutes, and finally the sputtering power is uniformly reduced from 130W to 60W within 23 minutes; at the same time, the sputtering power of the SiBCN target is uniformly reduced from 130W to 60W within 23 minutes, and then the sputtering power is uniformly increased from 60W to 130W within 23 minutes, and then the sputtering power is uniformly reduced from 130W to 60W within 23 minutes, and finally the sputtering power is uniformly increased from 60W to 130W within 23 minutes. After the experiment, the sample is naturally cooled to room temperature to obtain a four-layer SiBCN / DLC gradient film.

[0068] The performance of the gradient film prepared in this embodiment was tested, and the test results are as follows: Figure 1 to Figure 6 The results showed that the film thickness was about 500nm, the Vickers hardness was 766.6HV, the friction coefficient was 0.12, and it fluctuated greatly. The maximum transmittance of the film in the visible light range was 90%. The film-base bonding force began to break under a force of 200mN, cracks appeared at the edge of the scratch, and some peeling occurred.

[0069] Comparing Example 4 with Examples 2 and 3, it is found that the number of layers is not positively correlated with the binding force. As the number of layers of the gradient film increases, the rate of change of the power of the two targets accelerates. On the one hand, the difference in cluster size within the film begins to increase, and the clusters cannot form the densest stacking, which causes an increase in defects in the film. On the other hand, the large and continuous change in sputtering power prevents the graphite structure inside the sputtered particles from undergoing sufficient structural transformation, which will sacrifice the hardness of the film. When squeezed by external force, it is easy to cause cracks to expand, eventually leading to film shedding and cracking.

[0070] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0071] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a SiBCN / DLC gradient film, comprising the following steps: A) performing surface pretreatment on the substrate, SiBCN target and C target respectively; B) placing the SiBCN target and the C target in a magnetron sputtering chamber, sputtering the SiBCN target and the C target simultaneously, within the same sputtering time and the same sputtering power range, the sputtering power of the SiBCN target decreases, and the sputtering power of the C target increases, to obtain a SiBCN / DLC gradient film; In step B), the process of simultaneously sputtering the SiBCN target and the C target is specifically as follows: The sputtering power of target C was uniformly increased from 60W to 130W within 45min, and then uniformly decreased from 130W to 60W within 45min. At the same time, the sputtering power of SiBCN target was uniformly reduced from 130W to 60W within 45min, and then uniformly increased from 60W to 130W within another 45min; Or, the sputtering power of the C target is uniformly increased from 60W to 130W within 30min, then uniformly decreased from 130W to 60W within 30min, and finally uniformly increased from 60W to 130W within 30min; The sputtering power of the SiBCN target was uniformly reduced from 130 W to 60 W within 30 min, then uniformly increased from 60 W to 130 W within 30 min, and finally uniformly reduced from 130 W to 60 W within 30 min.

2. The preparation method according to claim 1, characterized in that: The surface pretreatment of the substrate is specifically as follows: The substrate was ultrasonically cleaned with detergent, acetone, alcohol and ultrapure water, and dried with nitrogen.

3. The preparation method according to claim 1, characterized in that: The surface pretreatment of the SiBCN target and the C target is specifically as follows: The SiBCN target and the C target are placed in a vacuum chamber at the same time, the vacuum degree is set to 0.75-1.25 Pa, the argon gas flow rate is set to 30-60 sccm, the sputtering power is set to 95-105 W, and the sputtering is performed for 10-20 minutes.

4. The preparation method according to claim 1, characterized in that: In step B), during the sputtering process, the magnetron sputtering chamber is evacuated to a vacuum of 1.5×10 -3 ~2.5×10 -3 Pa, temperature is 50-80℃, holding time is 10-20min, argon flow rate is 30-40sccm; adjust the butterfly valve to make the sputtering pressure 1-1.5Pa, and control the pressure for 10-20min.

5. The SiBCN / DLC gradient film prepared by the preparation method according to any one of claims 1 to 4, wherein the elements and element contents of each layer of the SiBCN / DLC gradient film vary in a gradient.

6. The SiBCN / DLC gradient film according to claim 5, characterized in that: The SiBCN / DLC gradient film has 1 to 4 layers and a thickness of 450 to 550 nm.

Citation Information

Patent Citations

  • Diamond-like carbon-based thin film and preparation method thereof

    CN108149193A

  • DLC (diamond like carbon) film hardened glass and preparation method thereof

    CN108191258A

  • Glass-based diamond-like carbon (DLC) composite hardness-increasing thin film capable of achieving visible light transmitting and preparation method thereof

    CN109797370A